2016
DOI: 10.1016/j.injury.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of outpatient visit after operative treatment of ankle fractures

Abstract: It is a common practice that patients have a scheduled follow-up visit with radiographs following ankle fracture surgery. The aim of this study was to evaluate whether an early outpatient visit (<3 weeks) after ankle fracture surgery resulted in a change in patient management. For this study, 878 consecutive operatively treated ankle fracture patients with an early outpatient clinical-radiological visit were reviewed. The outcome measure was a change in treatment plan defined as any procedure, medication, or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…None of the studies fulfilled the criteria for comparability, given that none controlled for baseline factors. Six studies (i.e., McDonald et al [ 19 ], Ovaska et al [ 20 ], Kempegowda et al [ 21 ], Weil et al [ 23 ], Stone et al [ 24 ], and Huffaker et al [ 25 ]) scored the maximum number of three points for the outcome domain. All other studies scored two points, mainly because no statement was made on the adequacy of follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies fulfilled the criteria for comparability, given that none controlled for baseline factors. Six studies (i.e., McDonald et al [ 19 ], Ovaska et al [ 20 ], Kempegowda et al [ 21 ], Weil et al [ 23 ], Stone et al [ 24 ], and Huffaker et al [ 25 ]) scored the maximum number of three points for the outcome domain. All other studies scored two points, mainly because no statement was made on the adequacy of follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…According to Stone et al [12], routine two-week post-operative radiographs for wrist fracture patients rarely result in changes in patient management [12]. Ovaska et al [11] recently studied the role of an outpatient visit after an ankle fracture surgery. The results suggested that routine radiographs would not be necessary at an early outpatient visit after ankle fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that routine radiographs would not be necessary at an early outpatient visit after ankle fracture surgery. However, 9.8% of 878 patients required a change in treatment plan post-operatively and only 37% of these patients had solicited earlier outpatient visit prior to scheduled follow-up visit, therefore it seems reasonable to continue these outpatient visits, since 6.2% of patients had a change in the treatment plan at the scheduled follow-up visit [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have questioned the value of routine radiographs obtained at the first outpatient clinic visit and at intermediate-to-late follow-up (i.e. after the initial 3 weeks) of operatively treated ankle fractures [ 18 , 19 ]. A recent retrospective analysis, involving a cohort of 528 patients with an ankle fracture, demonstrated that as few as 1.2% ( n = 11/928) of routine radiographs obtained after 3 weeks of follow-up led to a change in treatment strategy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%